Sustainable Mn-Ni-Co recovery from complex secondary resources through process-chain engineering and life-cycle environmental assessment - Meichen Pan; Yusheng Tang; Ziyuan Liu; Zhe Tan; Yibo Yang; Panpan Mu; Xiaoguang Zhang (Chemical Engineering Journal, 2026)

Microbial Perspective: Regulatory Mechanisms of Interactions Between Microplastics and Dissolved Organic Matter on Greenhouse Gas Emissions in Aquatic Ecosystems - Mengxin Xu; Meiqi Huang; Shuang Liu; Jinze He; Feng Zhao; Bo Shao; Guangli Mu; Hongyang Cui; Panpan Cui; Yingxin Zhao; Yiwen Liu; Xiaoyu Cui; et al. (Global Change Biology, 2026)
Microplastic (MP) pollution may influence aquatic greenhouse gas (GHG) emissions by altering dissolved organic matter (DOM)–microbe coupling, yet reported effects remain inconsistent across ecosystems and exposure regimes. Here, we synthesized evidence from 16 studies to quantify the net effects of MPs on CO 2 , CH 4 , and N 2 O fluxes under ambient DOM conditions. Our meta‐analysis indicates that MP exposure significantly increases CO 2 emissions and decreases N 2 O fluxes, whereas CH 4 responses show a non‐significant positive trend with high variability. Exposure duration and polymer identity emerge as key moderators, indicating that MP effects are context‐dependent rather than uniform. Short‐term exposure tends to suppress carbon mineralization, whereas long‐term exposure is more often associated with GHG production, consistent with a time‐dependent trajectory potentially shaped by polymer aging. Mechanistically, this pattern may reflect initial DOM adsorption and humification that reduce substrate availability, followed by the release of bioavailable MP‐derived compounds that may stimulate microbial respiration, methanogenesis, and denitrification. Overall, MPs reshape aquatic carbon and nitrogen cycling within the overarching framework of DOM, which may ultimately influence GHG emissions under certain conditions. These findings provide a quantitative basis for reconciling conflicting observations and improving predictions of the climate relevance of MP pollution in aquatic ecosystems.

Research progress on the separation, purification, and utilization of beryllium from beryllium-containing minerals - Mengchen Xiao; Yibo Yang; Yusheng Tang; Panpan Mu; Hao Liu; Xiaoguang Zhang; Dean Pan (Process Safety and Environmental Protection, 2025)

Green and sustainable strategy for separation and recovery of high-value fluorine and magnesium from fluorine slag by alkaline roasting-hydrometallurgy - Hang Zhao; Xiaoguang Zhang; Guosai Jiang; Feihua Yang; Yanling Wu; Panpan Mu; Haile Yan; De’an Pan (Journal of Environmental Chemical Engineering, 2025)

Research on extraction of valuable metals from solid waste by deep eutectic solvents - A review - Chenye Yang; Jianying Zhao; Panpan Mu; Guosai Jiang; Zhe Tan; Xiaoguang Zhang; Dean Pan (Process Safety and Environmental Protection, 2025)

Why are the Qinling Mountains Significant to China? - Xing Chen; Yanjun Shen; Qingyi Mu; Panpan Xu; Fenghao Duan; Jianbing Peng (Journal of Earth Science, 2025)

Study on the shielding of harmful components in spent FCC catalyst tailings - Haojie Zhang; Jianying Zhao; Panpan Mu; Xiaoguang Zhang; Shaogang Zhang; De’an Pan (Process Safety and Environmental Protection, 2024)

Efficient conversion process and mechanism of bromine in bromine-rich saline wastewater - Jixian Wu; Panpan Mu; Xiaoguang Zhang; Guosai Jiang; Zhe Tan; De'an Pan (Journal of Cleaner Production, 2024)

Preparation of chromium oxide by hydrothermal reduction of sodium chromate aqueous solution with hydrogen and application to chromite ore processing - Panpan Mu; Hongling Zhang; De'an Pan; Shuting Liang; Taiping Lou; Hongbin Xu (Hydrometallurgy, 2024)

Green recovery of Li, Ni, and Mn from spent xLi2MnO3·(1-x)LiMO2 cathode materials: Experimental study and mechanism analysis - Yifan Wang; Qijun Zhang; Xiaoxia Bai; Panpan Mu; Xiaoguang Zhang; Wei Wang; Zhe Tan; Zhenhuan Zhao; De'an Pan (Chemical Engineering Journal, 2023)